Answer:
![y^9](https://img.qammunity.org/2023/formulas/mathematics/college/65btkm710nut1dpp28hte44f9crkutob0i.png)
This is the same as saying y^9
===================================================
Step-by-step explanation:
When we apply the square root to the expression
, we end up with
![a^b](https://img.qammunity.org/2023/formulas/mathematics/college/w62wuaqywuj6ekxvp2coh8gwpha7jmm6u0.png)
![\sqrt{a^(2b)} = a^b](https://img.qammunity.org/2023/formulas/mathematics/college/urtmmtxjyqxnz6r8hwomxuiiwpjb37c5pw.png)
The exponent 2b divides in half to get b
Based on that rule, we can then say:
![\sqrt{y^(18)} = y^(18/2) = y^9](https://img.qammunity.org/2023/formulas/mathematics/college/3pqrrgo2hmyovmhkyt8yfrohwu4tm5vgw5.png)